An overview of language policy implementation in the City of Tswane Metropolitan Municipality with a focus on translation as an activity of language policy implementation - Seshoka, Keaobaka Omphile Precious (Rhodes University, Faculty of Humanities, School of Languages, 2016)
The South African Municipality Systems Act (2000) states that language should not act as a barrier of access for citizens with no or limited proficiency in English to municipal services, or in ensuring the right of citizens to participate in, and contribute to the social, cultural, intellectual, economic and political life of South African society. In that regard, it recommends that South African municipalities develop a culture of public participation by providing services in a language preferred and used by citizens within their municipality through translation, amongst other things. This study examines how the translation services, as articulated in the language policy and plan of the City of Tshwane Metropolitan Municipality, is used as a language implementation strategy and in facilitating public participation. It further assesses the quality of the translated information accessed by the different residents of the City of Tshwane Metropolitan Municipality against theories of translation appraisal. The main focus area of this research is on extent of the use of translation as an activity of corpus planning, to facilitate language policy implementation in the City of Tshwane Municipality to enable better public participation. It is hoped that the study will be able to give policy makers and those tasked with implementation, especially at government municipalities' strategies to assess and determine the state of translation services to improve functionality, quality and the extent to which translation activities contribute to corpus planning.
Keywords: Uncatalogued